2020
DOI: 10.1186/s12978-020-00925-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determinants of adolescent childbirth in Uganda- analysis of rural and urban women using six demographic and health surveys, 1988–2016

Abstract: Introduction: Uganda has high adolescent pregnancy. The details of adolescent childbirth and urban/rural patterns are scarce. We investigated the levels, time trends and determinants of adolescent childbirth in Uganda separately for urban and rural women. Methods: We estimated the percentage of women 20-24 years at each of the six Uganda Demographic and Health Surveys (1988/ 89, 1995, 2000/01, 2006, 2011 and 2016) who reported a live childbirth before age 20 years ("adolescent childbirth"), and examined change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…In Uganda, where adolescents constitute 34.8% of the total population, the Ministry of Health prioritises adolescents’ health by improving access to contraceptives, professional care during childbirth, and postnatal care; however, uptake remains low [ 9 ]. The 2020 Uganda Demographic and Health Survey [ 10 ] reported that 24.8% of girls aged 15–19 had begun bearing children. Over 30.4% of 15–19-year-old girls who require contraceptives are unable to access such services, while 17.2% of adolescent girls die because of childbirth-related complications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, where adolescents constitute 34.8% of the total population, the Ministry of Health prioritises adolescents’ health by improving access to contraceptives, professional care during childbirth, and postnatal care; however, uptake remains low [ 9 ]. The 2020 Uganda Demographic and Health Survey [ 10 ] reported that 24.8% of girls aged 15–19 had begun bearing children. Over 30.4% of 15–19-year-old girls who require contraceptives are unable to access such services, while 17.2% of adolescent girls die because of childbirth-related complications [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 3 Tackling the unmet need for FP among adolescents is critical especially in LMICs because it has significant implications on their reproductive health and well-being. 5 Adolescent childbearing has been associated with multiple adverse health outcomes, 6 7 and the literature also shows several challenges of the motherhood transition period for adolescents, which leave them disempowered with feelings of shame and embarrassment. 8–10 Specifically, concern has been raised about the unmet need for FP among postpartum women.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Unmet need for child spacing among women with adolescent births or repeat adolescent births have also been reported. 6 25 Lack of knowledge and access to general health services and youth-friendly FP care, in particular, are some of the key challenges affecting adolescent health in Uganda. 26 Evidence on the use of LAM in adolescents in LMICs are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Tackling the unmet need for FP among adolescents is critical especially in LMICs because it has significant implications on their reproductive health and wellbeing (Figaroa et al, 2020). Adolescent childbearing has been associated with multiple adverse health outcomes (Amongin et al, 2020a, Burke et al, 2018, and the literature also shows several challenges of the motherhood transition period for adolescents, which leave them disempowered with feelings of shame and embarrassment (Erfina et al, 2019, Mangeli et al, 2017, Watts et al, 2015. Specifically, concern has been raised about the unmet need for FP among postpartum women (Abraha et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that over 40% of pregnancies among Ugandan adolescents are unintended (Nalwadda et al, 2019) and there is an increasing occurrence of repeat adolescent births (<20 years) estimated at 56%, with a prevalence of short-birth intervals of 5.4% (Amongin et al, 2020b). Unmet need for child spacing among women with adolescent births or repeat adolescent births has also been reported (Amongin et al, 2020a, Amongin et al, 2020b. Lack of knowledge and access to general health services and youth-friendly FP care, in particular, are some of the key challenges affecting adolescent health in Uganda (Atuyambe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%